Estimation of the Wind Energy Potential in Various North Algerian Regions - Alliche, Mounir; Rebhi, Redha; Kaid, Noureddine; Menni, Younes; Ameur, Houari; İnç, Mustafa; Felemban, Bassem F. (Mdpi, 2021)
This investigation aims to model and assess the wind potential available in seven specific regions of North Algeria. These regions, i.e., Batna, Guelma, Medea, Meliana, Chlef, Tiaret, and Tlemcen, are known for their traditional agriculture. The wind data are obtained from the National Agency of Meteorology (NAM), and a Weibull distribution is applied. In the first part of this study, the wind potential available in these sites is assessed. Then, different models are used to estimate the wind system's annual recoverable energy for these regions. We are interested in wind pumping for possible use to meet the needs of irrigation water in rural areas. Four kinds of wind turbines are explored to determine the possibility of wind energy conversion. In addition, the effects of the heights of the pylon holding the turbines are inspected by considering four cases (10, 20, 40, and 60 m). This estimation showed that the annual mean wind velocity varies from 2.48 to 5.60 m/s at a level of 10 m. The yearly values of Weibull parameters (k and c) at the studied sites varied within 1.61-2.43 and 3.32-6.20 m/s, respectively. The average wind power density ranged from 11.48 (at Chlef) to 238.43 W/m(2) (at Tiaret), and the monthly wind recoverable potential varied from 16.64 to 138 W/m(2).
Keywords: Weibull distribution; wind potential; wind pumping; wind turbines; estimation